Analysis of Providing Stretching and Postural Physiotherapy Education during Handling of Upper Cross Syndrome, Neck Pain and Sleep Quality in Physiotherapists at PT Indo Sehat - Indasah; Surahman Sukron Rosyadi; Prima Dewi Kusumawati (Universitas STRADA Indonesia, 2025)
Background: Neck pain and upper cross syndrome (UCS) are common complaints among physiotherapists, often exacerbated by poor posture and repetitive tasks. These conditions can negatively impact sleep quality and overall work performance. Stretching and postural education are simple, non-invasive interventions that may reduce symptoms. Purpose: This study aimed to determine the effects of neck stretching and postural education on neck pain, upper cross syndrome, and sleep quality among physiotherapists at PT Indo Sehat. Methods: A true experimental, descriptive-analytical study was conducted over four weeks in four PT Indo Sehat clinics. Using proportional random sampling, 60 physiotherapists with a history of neck pain and poor sleep quality were selected and divided into intervention and control groups. Interventions included stretching routines and postural correction education. Data were collected through questionnaires and observation, and analyzed using paired and independent sample t-tests. Results: The intervention group showed statistically significant improvements in neck pain (p = 0.004), sleep quality (p = 0.000), and upper cross syndrome symptoms (p = 0.000). The control group showed limited or no significant improvement, especially in UCS (p = 0.061). Comparative analysis between groups showed meaningful differences pre- and post-intervention across all three variables (p < 0.005). Conclusion: Stretching and neck posture education significantly reduce neck pain and improve sleep quality and UCS symptoms in physiotherapists. These simple interventions are effective workplace strategies and are recommended for broader implementation.